Explaining women's success: technological change and the skill content of women's work - Sandra E. Black; Alexandra Spitz-Oener (Institute for the Study of Labor (IZA), 2007)
The closing of the gender wage gap is an ongoing phenomenon in industrialized countries. However, research has been limited in its ability to understand the causes of these changes, due in part to an inability to directly compare the work of women to that of men. In this study, we use a new approach for analyzing changes in the gender pay gap that uses direct measures of job tasks and gives a comprehensive characterization of how work for men and women has changed in recent decades. Using data from West Germany, we find that women have witnessed relative increases in non-routine analytic tasks and non-routine interactive tasks, which are associated with higher skill levels. The most notable difference between the genders is, however, the pronounced relative decline in routine task inputs among women with little change for men. These relative task changes explain a substantial fraction of the closing of the gender wage gap. Our evidence suggests that these task changes are driven, at least in part, by technological change. We also show that these task changes are related to the recent polarization of employment between low and high skilled occupations that we observed in the 1990s.
urn:nbn:de:101:1-20080401277
Keywords: 330; Frauenerwerbstätigkeit; Hochqualifizierte Arbeitskräfte; Lohndifferenzierung; Geschlecht; Schätzung; Deutschland